A Contested Invention at the Start of the Cold War: Uncle Sam, Progress and Identities Under the Gaze of Topaze in 1951 - Sosa-Vota, M (UNIV ARTURO PRAT, 2024)
At the start of the Cold War, the Chilean magazine Topaze condemned American interventionism in terms of economic, educational and foreign policy matters. The magazine s cartoons and articles represented an anti-imperialist approach in the context of Chilean magazines published in 1951, which generally legitimised the Western and North American political order, values and way of life. Patriotism resurfaces in this publication in order to condemn the Yankee presence, founded on the basis of Chile s heritage and wealth of natural resources. Consequently, the country s citizens are assured a place within a project of national identity. In the analysis of the magazine s contents, three aspects of social sovereignty can be identified that are linked to the popular susceptibility of its editorial line: political, economic and cultural. These formed the basis for articulating a sense of identity, which was created as a way of contesting neighbouring countries, North American capital and the hegemony of a foreign educational model. Without undermining or challenging social hierarchies, the magazine recognises popular culture as the repository of the nation s moral compass. The presence of Uncle Sam thus contributes to the creation of national unity, in the context of deepening the contradictions generated within a process of modernisation.